Alberto Fujimori : le populisme de l’efficacité - Diana Burgos-Vigna (Amnis)
Alberto Fujimori, President of Peru between 1990 and 2000, managed to remain popular by conducting a combination of traditional and new populist policies. This non-professional politician was able to come to power and remain in office in particular thanks to the lack of confidence in political parties and trade unions. He was immediately credited with honesty and competence. Throughout his successive terms of office, he developed a political strategy aimed at establishing his legitimacy. This strategy was based on the following measures: the setting up of a direct and almost emotional relationship with the most underprivileged classes through clientelist practices; the disintegration of the social fabric in order to prevent any opposition and strengthen the power of the Head of State; the instrumentalisation of certain groups, in particular via social programmes; lastly, the constant and ever-increasing control over information by keeping a close watch on the media and political opponents. Based on an image of efficiency, Alberto Fujimori’s policies remained popular until the end of the 1990s, when a series of corruption scandals precipitated the fall of his regime.